Applied Environmental Biotechnology: Present Scenario and Future Trends 2015
DOI: 10.1007/978-81-322-2123-4_10
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectrochemical Systems (BES) for Microbial Electroremediation: An Advanced Wastewater Treatment Technology

Abstract: Bioelectrochemical systems (BES) have been employed for various applications in recent years including energy production, wastewater treatment, electrosynthesis and desalination. The present chapter emphasizes the advantages and potential applications of BES for the remediation of recalcitrant pollutants present in various types of wastewaters. Bioelectricity generated from the treatment of these wastewaters is an additional energy output from the process along with the possible environmental solution. Since, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 130 publications
0
8
0
Order By: Relevance
“…This technology has interesting applications, including bioelectricity production, biogas production, wastewater treatment, and removal of toxic compounds . Currently, treatments with bioelectrochemical systems (BESs) have emerged as an interesting technology that can be used for the generation of bioelectricity from organic substrates obtained during wastewater treatment …”
Section: Introductionmentioning
confidence: 99%
“…This technology has interesting applications, including bioelectricity production, biogas production, wastewater treatment, and removal of toxic compounds . Currently, treatments with bioelectrochemical systems (BESs) have emerged as an interesting technology that can be used for the generation of bioelectricity from organic substrates obtained during wastewater treatment …”
Section: Introductionmentioning
confidence: 99%
“…This could be due to potentially negative influence on the organoleptic characteristics (in the case of food) or inadmissible change in the chemical and biological properties of the products subject to antioxidant protection (in the case of pharmaceuticals, ultra-pure and analytical chemicals, solutions of biologically active substances, etc.). Another drawback is related to the radical-chain reactions or pro-oxidant activities, which may occur in some cases after application of chemical antioxidants [29].…”
Section: Resultsmentioning
confidence: 99%
“…This occurs through chains of multifaceted microbial-electrochemical reactions. Mohanakrishna et al, 35 defined BES as a growing technology that employs microorganisms to convert chemical energy in wastewater to electrical energy through different microbial electrochemical reactions and devices. 36 Figure 1, presents an outline of various electrochemical devices, processes and techniques that comprise BES.…”
Section: Bioelectrochemical System (Bes)mentioning
confidence: 99%
“…Mohanakrishna et al, 35 reported that bioenergy could be generated from the microbial (catabolism or anabolism) reactions in BFCs. This is as a result of the process of an amalgamation between fermentation or putrefaction (or oxidation) and respiration (reduction) reactions.…”
Section: Overview Of Mechanisms In Bfcsmentioning
confidence: 99%